Application of Ijmālī Method In Exegesis (Sharḥ) The Hadith of The Prophet: Analysis of the Book of Hadith using the Ijmālī Method - Muhammad Qomarullah (Jurnal Ushuluddin, 2022)
The Ijmālī method in interpreting hadith or Sharḥ hadith is an old method for interpreting the Qur'an as done by previous scholars. This Ijmālī method includes a method that does not require a fairly in-depth discussion of the hadith, but the sharah of the hadith is sufficient globally and is only general in nature. This article aims to explain the sharah of hadith by using the Ijmālī method as a method of discussing interpretations. This article is a library research. The results showed that the application of this method using a language approach, then briefly using another hadith with the same narrator as bi al-ma'na, discussed the meaning globally and not in depth. For this reason, supporting sciences such as language, 'Ulumul Qurān, and 'Ulumul Hadith are needed for someone who is called a scholar to explain the Sharḥ of hadith, such as riwāyah science and Dirāyah science as well as Gharīb al-Ḥad Science in Ma'āni al-Ḥadīṡ Science. The disadvantage of the Ijmālī Method is that someone who wants to explore the meaning of hadith cannot gain deep and thorough knowledge